PENGARUH LATIHAN DOUBLE LEG CONE HOP DAN LUNGES TERHADAP KEKUATAN TENDANGAN LONG PASS PEMAIN SSB INTERNAL FC U-19 - Kartika Septianingrum (Universitas Majalengka, 2022)
This study aims to determine the effect of the practice of duoble leg cone hops and lunges on the level of long pass ability of SSB Internal FC soccer players, Ngawi. This study uses an experimental method with a